Kerja Sama Antara Orang Tua dan Sekolah dalam Mendukung Anak Berkebutuhan Khusus ke Sekolah - Putri Mutiara Jwinarti; Syaidah Upara; Opi Andriani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
Collaboration between parents and schools plays a very important role in supporting children with special needs in their educational process. This article explores the importance of effective collaboration between parents and educators in a joint effort to understand, plan, and provide appropriate support for children with special needs. This article uses survey and interview research methods at SD N 23/VI Rantau Panjang I. Based on the results of the research that has been carried out, it can be concluded that the importance of cooperation between parents and schools in supporting children with special needs. The form of cooperation between educational institutions and parents in recognizing the character of early childhood children with special needs is by 1). Carrying out early detection of students, 2). Carrying out parent meeting classes, 3). Carrying out parent consultation days, 4). Collaborating with psychologists/therapists if necessary.